Cognitive Flexibility of Students in Solving Mathematical Problems: A Phenomenology Study - Rama Nida Siregar; Didi Suryadi; Sufyani Prabawanto; Abdul Mujib (Universitas Negeri Semarang, 2022)
The importance of students' cognitive flexibility abilities in solving mathematical problems is the driving force behind this research. This study's goal was to identify and characterize students' levels of cognitive flexibility in handling mathematical problems in light of the indicators. This kind of study uses qualitative research techniques and a phenomenological design. The instrument employed is a test of problem-solving skills that has been supplemented with markers of cognitive flexibility to see the talents that have been assessed and interviews to learn more in-depth. In this study, data on students' capacities for cognitive flexibility in solving mathematical problems were collected and analyzed utilizing exams for such problem-solving and the indicators employed. Two markers of cognitive flexibility are included in this examination of mathematical problem-solving skills: (1) offering several interpretations of a picture, story, or mathematical issue, and (2) applying a variety of mathematical problem-solving techniques. According to the findings of this study, 5 participants fell into the flexible category, 6 people fell into the somewhat flexible category, and 4 participants fell into the less flexible category when it came to their ability to solve mathematical problems. The research's relevance is that future researchers and educational practitioners can attempt to construct learning to improve students' cognitive flexibility abilities in solving mathematical issues. This can be investigated in topics other than social arithmetic. Latar belakang penelitian ini yaitu pentingnya kemampuan cognitive flexibility siswa dalam pemecahan masalah matematis. Penelitian ini bertujuan untuk mengetahui serta mendeskripsikan kemampuan cognitive flexibility siswa dalam pemecahan masalah matematis berdasarkan indikatornya. Jenis penelitian ini adalah desain fenomologi dengan metode kualitatif. Adapun penggunaan tes kemampuan pemecahan masalah yang telah diliputi indikaor kemampuan cognitve flexibilty untuk melihat kemampuan cognitive flexibilty yang telah diujikan dan wawancara untuk mengetahui lebih mendalam merupakan instrumen penelitian ini. Dalam penelitian ini, data diperoleh untuk melihat kemampuan cognitive flexibility siswa dalam pemecahan masalah matematis yang dianalisis menggunakan tes pemecahan masalah matematis berikut indikator nya. Tes pemecahan masalah matematis ini memuat dua indikator kemampuan cognitive flexibility yaitu: 1) memberikan berbagai penafsiran terdapat suatu gambar, cerita, atau masalah matematis; dan 2) menggunakan beragam strategi penyelesaikan masalah matematis. Kesimpulan yang diperoleh dalam penelitian ini terkait kemampuan cognitive flexibility siswa dalam pemecahan masalah matematis sebanyak 5 partisipan berada pada kategori fleksibel, 6 partisipan berada pada kategori cukup fleksibel, dan 4 partisipan berada pada kategori kurang fleksibel. Sehingga implikasi dalam peneltian adalah agar para peneliti selanjutnya maupun praktisi pendidikan dapat berupaya mendesain pembelajaran untuk meningkatkan kemampuan cognitive flexibility siswa dalam pemecahan masalah matematis dan dapat diteliti pada materi lain selain aritmatika sosial.